Debonding Resistance of Various Glass Ionomer Cements to Saliva-Contaminated Dentin: An in vitro Study - Krishnani, Karishma A; Shetty, Shreema (International Journal of Dental Materials, 2025)
Background: Glass ionomer cements (GICs) are widely used in dentistry as they can effectively bond to the tooth structure and release fluoride ions. However, saliva contamination during the setting process can impair bond strength and reduce the longevity of the restoration. Aim: To evaluate the debonding resistance of different glass ionomer cements with saliva-contaminated dentin. Materials and methods: Forty-five extracted human premolar teeth were embedded in an acrylic block. The teeth were sectioned until the dentin surface was exposed and contaminated with saliva. Then, the Poly-tetra-fluoro-ethylene tube was placed on the dentin surfaces of the specimens, and the different glass ionomer cement mixes, type IX GIC, resin-modified GIC (RMGIC), and hybrid GIC, were condensed into it. The specimens were subjected to 500 cycles of thermocycling for 20s at 5º to 55º temperature and were stored in distilled water for 10 days. Debonding resistance of the specimens was measured using a universal testing machine (UTM). The specimen was mounted on the UTM, and the load was applied at a crosshead speed of 1 mm per minute until debond occurs. The obtained data was subjected to one-way ANOVA analysis followed by post-hoc analysis. Results: Light-cure RMGIC showed the highest debonding load (45.358 ± 15.171 N), followed by Type-IX GIC (8.048 ± 3.717 N) and Hybrid GIC (7.574 ± 3.501 N). One-way ANOVA showed significant differences among groups (p=0.000). The pair-wise comparison revealed light-cure RMGIC differed significantly from Type-IX and Hybrid GIC (p=0.000), while Type-IX and Hybrid GIC showed no significant difference (p=0.989). Conclusion: Light-cure RMGIC exhibited superior debonding resistance compared to Type-IX and Hybrid GICs.